Protective effect of Devosia sp. ANSB714 on growth performance, serum chemistry, immunity function and residues in kidneys of mice exposed to deoxynivalenol. (June 2016) - Zhao, Lihong; Li, Xiaoying; Ji, Cheng; Rong, Xiaoping; Liu, Shujing; Zhang, Jianyun; Ma, Qiugang
Abstract: This study was conducted to investigate the toxic effects of deoxynivalenol (DON) and the ameliorating efficacy of Devosia sp. ANSB714 for the negative effects of DON on mice. In the experiment, 80 mice were randomly divided into 4 treatments: non-toxin control, toxin, non-toxin control + ANSB714 and toxin + ANSB714. During 28 days, the mice in treatment with 4.70 mg/kg DON only had significantly lower average daily gain as compared those with non-toxin control treatment ( P  < 0.05). Serum blood urea nitrogen, tumour necrosis factor-α and the residues of DON in kidneys in mice received the toxin diet were obviously higher than those with non-toxin control ( P  < 0.05). There were no significant differences ( P  > 0.05) between ANSB714 treatments and non-ANSB714 treatments on above parameters of mice. Adding ANSB714 to toxic diets could normalize deviant physiological effects of DON on mice. Highlights: Deoxynivalenol (DON) reduced growth performance of mice. DON negatively affected serum chemistry and immunity function of mice. DON led to the residues of DON in kidneys on mice. The DON diet with D evosia sp. ANSB714 eliminated effects of the DON.